MiniMelt: An instrument for real-time tracking of electron beam additive manufacturing using synchrotron x-ray techniques - König, Hans Henrik; Semjatov, Nick; Spartacus, Gabriel; Bidola, Pidassa; Ioannidou, Chrysoula; Ye, Jihui; Renner, Jakob; Lienert, Ulrich; Abreu-Faria, Guilherme; Wahlmann, Benjamin; Wildheim, Martin; Ackelid, Ulf; et al. (Review of Scientific Instruments, 2023)
The development of a sample environment for in situ x-ray characterization during metal Electron Beam Powder Bed Fusion (PBF-EB), called MiniMelt, is presented. The design considerations, the features of the equipment, and its implementation at the synchrotron facility PETRA III at Deutsches Elektronen-Synchrotron, Hamburg, Germany, are described. The equipment is based on the commercially available Freemelt ONE PBF-EB system but has been customized with a unique process chamber to enable real-time synchrotron measurements during the additive manufacturing process. Furthermore, a new unconfined powder bed design to replicate the conditions of the full-scale PBF-EB process is introduced. The first radiography (15 kHz) and diffraction (1 kHz) measurements of PBF-EB with a hot-work tool steel and a Ni-base superalloy, as well as bulk metal melting with the CMSX-4 alloy, using the sample environment are presented. MiniMelt enables time-resolved investigations of the dynamic phenomena taking place during multi-layer PBF-EB, facilitating process understanding and development of advanced process strategies and materials for PBF-EB.<br
CRIS-Team Scopus Importer:2023-12-15